Muscle hypertrophy is correlated with load progression delta, climb volume, and total load volume in rodents undergoing different ladder-based resistance training protocols - Krause Neto, Walter; Silva, Wellington de Assis; de Oliveira, Tony Vinicius Apolinário; Vilas Boas, Alan Esaú dos Santos; Ciena, Adriano Polican [UNESP]; Anaruma, Carlos Alberto [UNESP]; Gorzi, Ali; Caperuto, Érico Chagas; Gama, Eliane Florencio (Elsevier, 2022)
We compared the effects of two ladder-based resistance training (LRT) protocols on the skeletal muscle morphology (biceps brachialis and plantaris) of Wistar rats. Also, we correlated the training parameters with the muscle fiber cross-sectional area (fCSA). After maximum load tests (ML), twenty-nine young adult Wistar rats were divided into: CONTROL (n = 9), LIMITED (n = 10, 6–8 climb [2 × 50 %ML, 2 × 75 %ML, 2 × 100 %ML, and 2 × 100 %ML+30 g]) and UNLIMITED (n = 10, ≥4 climbs [50 %ML, 75 %ML, 90 %ML, 100 %ML + 30 g until failure) LRT. After eight weeks, the main results were: 1) For biceps brachialis, the type I, IIa, and mean fCSA was statistically larger in the LIMITED than CONTROL. The nuclei/fiber ratio was statistically higher in the LIMITED and UNLIMITED. The correlations found between total load, absolute delta load, and relative load and fCSA were moderate. 2) For plantaris, the type I, IIa, IIx/b, and mean fCSA was statistically larger in the LIMITED than CONTROL. The type IIa, IIx/b, and mean fCSA was statistically larger in the UNLIMITED than CONTROL. The nuclei/fiber ratio was statistically higher in both trained groups than CONTROL. The correlation between the climbing number, total load, and the fCSA was moderate. The correlation between delta absolute load and fCSA was strong. We concluded that rodents submitted to high-intensity, high-volume LRT, but limited climbing volume per session, presented more significant type I, IIa, IIx/b, and mean fCSA, higher nuclei/fiber ratio, and greater maximum carrying capacity. Also, muscle hypertrophy correlated positively with the load progression, training volume, and total load.
Keywords: Cross-sectional area; Hypertrophy; Morphology; Resistance training; Skeletal muscle